Writing the Reader. Configurations of a Cultural Practice in the English Novel - Birke, Dorothee (linguae & litterae, 2016)
The history of the novel is also a history of shifting views of the value of novel reading. This study investigates how novels themselves participate in this development by featuring reading as a multidimensional cultural practice. English novels about obsessive reading, written in times of medial transition, serve as test cases for a model that brings together analyses of form and content.